Efl students’ perceptions about a web-based english reading comprehension course (2012)
Web-based distance education is an innovative modality of instruction in Colombia. It is characterized by the separation of the teacher and learners, the use of technological tools and the students’ autonomy development. This paper reports the findings of a case study that explores students’ perceptions about an English reading comprehension course in a web-based modality. Findings show that students havedifferent opinions about the course, its content and objectives, its level of difficulty, the time students invested in the course, adults’ learning, and the role of the teacher. We perceived that this course represents an academic challenge; it is conducive to learning, and favors students’ autonomous use of time.La educación virtual es una modalidad de instrucción innovadora en Colombia. Se caracteriza por la separación del profesor y los estudiantes, el uso de recursos tecnológicos y el desarrollo de su autonomía. Este artículo muestra los hallazgos de un estudio de caso que explora las opinionesde los estudiantes acerca de la educación virtual. Se revelan las diferentes creencias sobre el curso, su contenido, objetivos y nivel de dificultad, el tiempo invertido por los estudiantes y el papel del profesor. Encontramos que este curso puede ser considerado como un desafío académico en el que se facilita el aprendizaje y el uso autónomo del tiempo.